PENGARUH KUALITAS PELAYANAN SERVICE MOBIL SUZUKI TERHADAP KEPUASAN KONSUMEN PADA PT MEGAHPUTRA SEJAHTERA MAKASSAR - Ali Baba (Jurnal Bisnis dan Kewirausahaan, 2017)
The aim of this research is to investigate and analyze the impact of service quality Suzuki car service affects customer satisfaction at PT. Prosperous Megahputra Makassar. Data used in this study are primary data that the questionnaire answers of respondents with data analysis using multiple linear regression with SPSS 20. The sample in this study as many as 100 people as respondents in this study. Suzuki car service quality service (tangible, empathy, realibility, responsiveness and assurance) positive and significant impact on customer satisfaction in PT. Prosperous Megahputra Makassar. This means that the implementation of service quality service are rated by customers on forms of real actualization perceived komsumen meet customer expectations.